1975
DOI: 10.1111/j.0954-6820.1975.tb04897.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Death and Circulating Anticoagulant (“Antithromboplastin”)

Abstract: A report is presented of a young, otherwise apparently healthy, woman who had had three pregnancies which for some unknown reason terminated in intrauterine death (macerated foetuses). During the third pregnancy a coagulation defect was diagnosed, which was characterized by prolonged coagulation times and prolonged one‐stage prothrombin time. This defect disappeared after the end of the pregnancy, but returned during the fourth pregnancy. This time a circulating anticoagulant was found, which inhibited the act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(34 citation statements)
references
References 18 publications
1
33
0
Order By: Relevance
“…The first such case report suggesting this correlation was published in 1975 and described the presence of a circulating anticoagulant in a woman with recurrent abortions. 11 This anticoagulant was later found to be the lupus anticoagulant. Since that time many studies have confirmed the association of ADs such as antiphospholipid syndrome, 12 rheumatoid arthritis 13 and systemic lupus erythematosus, 14,15 with miscarriage.…”
Section: Autoimmune Diseases and Miscarriagementioning
confidence: 98%
“…The first such case report suggesting this correlation was published in 1975 and described the presence of a circulating anticoagulant in a woman with recurrent abortions. 11 This anticoagulant was later found to be the lupus anticoagulant. Since that time many studies have confirmed the association of ADs such as antiphospholipid syndrome, 12 rheumatoid arthritis 13 and systemic lupus erythematosus, 14,15 with miscarriage.…”
Section: Autoimmune Diseases and Miscarriagementioning
confidence: 98%
“…A higher incidence of RPL has been documented for both low-risk and high-risk pregnancies with antiphospholipid antibodies (aPL; (Empson et al 2002;Subrt et al 2008). Antiphospholipid antibodies are thought to lead to fetal loss by causing thrombosis of the placental vessels, although the observed variability in placental pathology somehow argues against such a direct involvement (Nilsson et al 1975;Salafia and Cowchock 1997). Lowered expression of ANXA5 in placentas of M2 haplotype carriers ) could be potentially responsible for reduced coverage of phospholipid trophoblast surfaces and hence lead to an increase in the number of exposed available antigenic determinants for the generation of aPL.…”
Section: Apl Antibodies and M2 Haplotype Of Anxa5mentioning
confidence: 99%
“…Since then, the association between the presence of aPL and the occurrence of repeated spontaneous abortions has been extensively reported [2][3][4][5][6][7]. Antiphospholipid antibodies are a leading cause of pregnancy loss and pregnancy-related morbidity.…”
Section: Apl Antibodies and Pregnancy Lossmentioning
confidence: 99%